The use of the long modular diagnostics shield module to mitigate shutdown dose rates in the ITER diagnostics equatorial ports. (16th March 2018) - Juárez, R.; Guirao, J.; Kolsek, A.; Lopez, A.; Pedroche, G.; Bertalot, L.; Udintsev, V.S.; Walsh, M.J.; Sauvan, P.; Sanz, J.
Abstract: The ITER equatorial port plugs are submitted to a drained weight limit of 45 T. This limitation can conflict with their radiation shielding demands, although some weight margin is being discussed. The port interspaces are subject to a shutdown dose rate limit of 100 µ Sv h −1 after 10 6 s of cooling time. To meet it, the port plugs must show a neutron flux attenuation comparable to their neighborhood, despite considering penetrations to host systems. Most of this task relies on the drawer shield module (DSM). In this work, two DSM concepts are analyzed with this perspective: the box-based DSM and the modular DSM. Regardless the penetrations, the box-based DSM leads to unsatisfactory port plugs to meet both weight and SDDR requirements. On the contrary, the modular DSM shows a performance which allows for the adoption of such DSM concept, or equivalent, a port may comply with both requirements at the same time, provided the penetrations are well designed.